Screening of Multiple Myeloma by Polyclonal Rabbit Anti-Human Plasmacytoma Cell Immunoglobulin - Mu, Bo (Public Library of Science, 2013)
Antibody-based immunotherapy has been effectively used for tumor treatment. However, to date, only a few tumor-associated antigens (TAAs) or therapeutic targets have been identified. Identification of more immunogenic antigens is essential for improvements in multiple myeloma (MM) diagnosis and therapy. In this study, we synthesized a polyclonal antibody (PAb) by immunizing rabbits with whole human plasmacytoma ARH-77 cells and identified MM-associated antigens, including enlonase, adipophilin, and HSP90s, among others, via proteomic technologies. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assay showed that 200 µg/mL PAb inhibits the proliferation of ARH-77 cells by over 50% within 48 h. Flow cytometric assay indicated that PAb treatment significantly increases the number of apoptotic cells compared with other treatments (52.1% vs. NS, 7.3% or control rabbit IgG, 9.9%). In vivo, PAb delayed tumor growth and prolonged the lifespan of mice. Terminal deoxynucleotidyl transferase dUTP nick end labeling assay showed that PAb also induces statistically significant changes in apoptosis compared with other treatments (P<0.05). We therefore conclude that PAb could be used for the effective screening and identification of TAA. PAb may have certain anti-tumor functions in vitro and in vivo. As such, its combination with proteomic technologies could be a promising approach for sieving TAA for the diagnosis and therapy of MM.